Study of clinical presentation, management and prognosis of liver abscess - Surendran, S.; Vallipriya, V. (International Surgery Journal, 2022)
Background: The term "liver abscess" refers to a collection of pus in the parenchyma of the liver mainly due to the infection of microorganisms. If a liver abscess is not diagnosed early or not treated, it can be fatal, resulting in significant morbidity and mortality. Aim of the study was to study the clinical manifestations, aetiologies, and management of liver abscesses in tertiary care hospital patients. Methods: From March 2015 to August 2016, 99 patients with liver abscesses were studied in the general surgery wards of government Rajaji hospital in Madurai. In the beginning, routine examination history and blood tests were documented. Then, an ultrasound was performed in selected cases, and further treatment was performed. Results: In the current study, the most cases (48%) were from the age group of 41-50 years. We discovered that this disease is more common in men (97.97%), mainly with a history of alcohol intake, with an amoebic liver abscess (ALA) in 95% of cases. Abdominal pain (100%) and fever (57%) were the most common symptoms observed in the patients. For treatment, we used single aspiration in 30 (30.3%) cases, percutaneous catheter drainage in 25 (25.25%) cases, laparotomy and drainage in 22 (22.22%) cases, multiple aspirations in 19 (19.09%) cases, and conservative management in 3 (3.03%) of the cases. Conclusions: Liver abscesses are most commonly found in young males with a history of alcohol consumption. Unfortunately, it is still a disease that causes significant morbidity. To successfully manage the liver abscess aspiration, catheter drainage and laparotomy with drainage can be used, whether single or multiple.